Oxygen Enriched Oxamides and N‐Dinitrated Oxamides: Trinitroethyl Esters, Nitrocarbamates and Nitrates. Issue 33 (1st September 2021) - Klapötke, Thomas M.; Krumm, Burkhard; Reith, Thomas; Riedelsheimer, Christian
Abstract: Starting from the readily available starting materials diethyl oxalate, glycine and β‐alanine, some new N ‐nitrated oxamides were synthesized. Oxamides formed by condensation reactions were subsequently nitrated to form the corresponding dinitroxamides. These were further converted to the corresponding acid chlorides with the utilization of thionyl chloride. The final reaction of the β‐alanine based dinitroxamide with trinitroethanol generated the energetic target ester in moderate yield and high purity. Additionally, starting from diethyl oxalate and ethanolamine gave access to a nitrocarbamate based on an oxamide. Furthermore, the previously reported compound bis(2‐nitratoethyl) oxamide was synthesized now in a more facile fashion and fully characterized, especially in case of the energetic properties, sensitivities and crystal structure. The compounds were fully analysed by NMR spectroscopy, vibrational analysis and elemental analysis. The heat of formation was calculated with the Gaussian program package and in combination with the experimental density the energetic properties were estimated utilizing the Explo 5 computer code. Abstract : Various oxamide precursors were synthesized and further converted into trinitroethyl ester, nitrocarbamate and nitrate of oxamides and nitroxamides. All compounds were fully characterized including their thermal and sensitivity stability. Furthermore, the energetic properties were calculated by using Gaussian program package in combination with the experimental density and the Explo 5 computer code.